How to build an Encyclopedia for the 21st Century: Lessons learned from The Great Norwegian Encyclopedia - Erik Bolstad; Stig Arild Pettersen (Studia Lexicographica)
After more than 100 years of existence, Norway’s Great Norwegian Encyclopedia went through a major crisis between 2010 and 2014, as the transformation to the new, digital reality became commercially unviable to the publishing house that owned it. The country’s universities came together, formed The Great Norwegian Encyclopedia Association, and created a new editorial team, which has transformed the encyclopedia into an online success with high-quality articles assessed and updated by some of Norway’s leading scholars. The partnership with academia, a purpose-made publishing software, a decentralized production model, and confidence in the original brand have been keys to building this public service encyclopedia that other, likeminded institutions across Europe can learn from.